Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.ajur.2020.05.008
|View full text |Cite
|
Sign up to set email alerts
|

A decade of trends in the distribution and antimicrobial susceptibility of prevalent uropathogens among pediatric patients from Tehran, Iran during 2005–2016

Abstract: Objectives To determine changes in the distribution of uropathogens and their antimicrobial resistance in pediatric patients in a children's hospital from 2005 to 2016. Methods A cross-sectional analysis of uropathogens and their antimicrobial resistance within inpatient children was performed over the 11-year period, 2005 to 2016, in Ali Asghar children's hospital. The rate of antibiotic resistance among patients was evaluated according to demographic data including ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…These results concur with a study conducted in 2021 in Tehran, which identified E. coli as the most frequent etiological agent underlying UTI in children (77.6%) [19]. Other studies from additional nations have confirmed this finding [20][21].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These results concur with a study conducted in 2021 in Tehran, which identified E. coli as the most frequent etiological agent underlying UTI in children (77.6%) [19]. Other studies from additional nations have confirmed this finding [20][21].…”
Section: Resultssupporting
confidence: 91%
“…Two previous studies, from France in 2017 [27] and from Greece in 2020 [28] determined that amikacin was the optimal antibiotic for treating UTIs in children and infants; those results concur with the sensitivities identified in this study. However, in contrast, a 2021 study from Tehran, Iran reported the high degree of resistance of Gram-negative organisms to amikacin, ceftriaxone, and imipenem [29]. A study conducted in Pakistan also described organisms that were extremely resistant to a range of antimicrobial agents like cefixime, ceftriaxone, ciprofloxacin, and nalidixic acid [30].…”
Section: Resultsmentioning
confidence: 99%
“…Eleven year prolong study conducted from 2005-2016 at Iran shows resistance pattern of Pseudomonas as follows 6.9 % resistance to amikacin, 100% resistance to ampicillin, 46.15% resistance to ceftriaxone, 4% resistance to ciprofloxacin, and 83.87% resistance to nitrofurantoin. 27 Following is the resistance pattern of our study for Pseudomonas: none of the isolates of pseudomonas was resistance to amikacin 1.3 % resistant to ampicillin, 1.2% and 0.9% resistance to ciprofloxacin and ceftriaxone respectively and 18.2% isolates were resistant to nitrofurantoin.…”
Section: Discussionmentioning
confidence: 62%
“…It is worth mentioning that in our study, the male infants showed a higher total number of positive cultures (56%) than female infants (44%). The difference might be attributed to young males' lack of circumcision at this age [ 20 ]. Interestingly, our statistical results showed that Egyptian infants (less than one year) were equally susceptible to E. coli and Klebsiella spp (36% and 38%, respectively).…”
Section: Discussionmentioning
confidence: 99%